Non-standard bifurcation approach to nonlinear elliptic problems - Silva, Willian Cintra da (2020)
Bifurcation is a very useful method to prove the existence of positive solutions for nonlinear elliptic equations. The existence of an unbounded continuum of positive solutions emanating from zero or from infinity can be deduced in many problems. In this paper, we show the applicability of this method in some problems where the classical bifurcation results can not be directly applied.